Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1088/0022-3727/40/14/014
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum arc velocity and erosion rate measurements on nanostructured plasma and HVOF spray coatings

Abstract: Arc velocity and erosion rate measurements were performed on nanostructured pure Cu cathodes in 10−5 Torr vacuum (1.3324 m Pa), in an external magnetic field of 0.04 T. Five different kinds of nanostructured cathodes were produced by spraying pure Cu powders of three different sizes, on Cu coupons by atmospheric pressure plasma spraying and high velocity oxygen fuel spraying techniques. The erosion rates of these electrodes were obtained by measuring the weight loss of the electrode after igniting as many as 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
(28 reference statements)
0
8
0
4
Order By: Relevance
“…Так, у [28] проводилось моделювання дугового розряду на мідних катодах, а у [29]дослідження впливу електричних та магнітних полів у дуговій плазмі при синтезі одностінних вуглецевих нанотрубок. Проведено також експериментальне дослідження впливу товщини наноструктурованого шару на фізичні властивості вольфрамового катода [30,31] та швидкість ерозії на наноструктурованих мідних катодах [32]. Проводились і деякі дослідження дугових плям [33,34].…”
Section: вступunclassified
See 3 more Smart Citations
“…Так, у [28] проводилось моделювання дугового розряду на мідних катодах, а у [29]дослідження впливу електричних та магнітних полів у дуговій плазмі при синтезі одностінних вуглецевих нанотрубок. Проведено також експериментальне дослідження впливу товщини наноструктурованого шару на фізичні властивості вольфрамового катода [30,31] та швидкість ерозії на наноструктурованих мідних катодах [32]. Проводились і деякі дослідження дугових плям [33,34].…”
Section: вступunclassified
“…Також розглянемо можливі джерела і стоки тепла в електродах як з нерухомими плямами, так і з плямами, що переміщуються з деякою швидкістю. В експериментальних дослідженнях [30,31] було показано, що на електродах присутні як ті, так і інші види плям.…”
Section: теоретичний розгляд процесівunclassified
See 2 more Smart Citations
“…Specifically for Cu cathodes, the presence of O in the cathode and/or the presence of a certain amount of an oxidizing gas are known to reduce cathode erosion significantly [1,6]. In addition to the above-mentioned factors, the cathode microstructure is also known to affect arc erosion rates [11][12][13]. Researchers have shown that surface properties such as surface micro-protrusions, roughness, impurity inclusions and microstructure of the cathode (grain size, second phase or particles, features such as solute concentration and defect structure) significantly affect the break-down voltage and dielectric strength [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%